Mapping the Interface of a GPCR Dimer: A Structural Model of the A2A Adenosine and D2 Dopamine Receptor Heteromer - Borroto-Escuela, Dasiel O.; Rodriguez, David; Romero-Fernandez, Wilber; Kapla, Jon; Jaiteh, Mariama; Ranganathan, Anirudh; Lazarova, Tzvetana; Fuxe, Kjell; Carlsson, Jens (Frontiers in Pharmacology, 2018)
The A2A adenosine (A2AR) and D2 dopamine (D2R) receptors form oligomers in the cell membrane and allosteric interactions across the A2AR-D2R heteromer represent a target for development of drugs against central nervous system disorders. However, understanding the molecular determinants of A2AR-D2R heteromerization and the allosteric antagonistic interactions between the receptor protomers is still limited. In this work, a structural model of the A2AR-D2R heterodimer was generated using a combined experimental and computational approach. Regions involved in the heteromer interface were modelled based on the effects of peptides derived from the 14 transmembrane (TM) helices on A2AR-D2R receptor-receptor interactions in bioluminescence resonance energy transfer and proximity ligation assays. Peptides corresponding to TM-IV and TM-V of the A2AR blocked heterodimer interactions and disrupted the allosteric effect of A2AR activation on D2R agonist binding. Protein-protein docking was used to construct a model of the A2AR-D2R heterodimer with a TM-IV/V interface, which was refined using molecular dynamics simulations. Mutations in the predicted interface reduced A2AR-D2R interactions in bioluminescence resonance energy transfer experiments and altered the allosteric modulation. The heterodimer model provided insights into the structural basis of allosteric modulation and the technique developed to characterize the A2AR-D2R interface can be extended to study the many other G protein-coupled receptors that engage in heteroreceptor complexes.